The Framework for Development of Web-Based Constructivist Learning Environment Model to Promote Critical Thinking Integration with Neuroscience - Wetpichetkosol, Bhudtree; Chaijaroen, Sumalee (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 29 No 2 (2561): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2018.22, 2018)
The purpose of this study was to synthesize theoretical framework and designing framework development of the web-based constructivist learning environment model to promote critical thinking integration with neuroscience. Research design was Model research phase I: Model development. The procedures will be as following; 1) to examine the principles and theories, 2) to explore the instructional context, and 3) to synthesize the theoretical framework and the designing framework of the web-based constructivist learning environment model to promote critical thinking integration with neuroscience. The result revealed that: the theoretical framework consists of 6 foundation bases; 1) Contextual Base, 2) Psychological Base, 3) Pedagogical Base, 4) Technological Base and Media Theory Base, 5) Critical Thinking Base, and 6) Neuroscience Base. The development of web-based constructivist learning environment model to promote critical thinking integration with neuroscience comprises of 7 components as follows; (1) Problem Center, (2) Knowledge Center, (3) Cognitive Tool Center, (4) Collaboration Center, (5) Critical Thinking Care Center, (6) Scaffolding Center, and (7) Coaching Center. Keywords: constructivist, web-based learning environment, critical thinking